Stabilizing Muslim Marriages: Some Reflections on Ethical Dimension of Family Law Reform - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas Bin (Mazahib, 2017)
Marriage breakdowns and family instability with their debilitating after-effects on women and children are the hallmark of greatly mechanized global community at present time. To remedy the situation, social scientists have diagnosed a multitude of variables as the precursor for the upward trends in marriage breakdowns and family disintegration. In Malaysian context, women`s financial independence, easy access to multimedia and early marriage are among the factors which account for the rising phenomenon of divorce even during the early years of marriage among Muslims.Â  To remedy the situation, marriage counseling, law reform and pre-marriage courses are mostly emphasized by both mainstream legal scholars and women right activists. It is my considered opinion that these formalistic approaches if not integrated with the emphasis on ethical side of Islamic law may cause more marriage breakups than enhancing families.Â  The bigger issues in terms of ethical management of Muslim family, such as marriage fidelity, sense of commitment to care for women and children, and spousal mutual empathy and responsibility may help a great deal in acculturating our society from early childhood to adolescence and through adulthood. The paper, therefore, argues for the more concentrated ethical approach for addressing the underlying causes of marriage disability in order to give more effect and meaning to the existing formalistic social and legal measures by reforming Muslims` mindset and outlook towards family. Keywords: family disability and marriage breakdowns in Malaysia, ethical management.